Efficiency of Black Soldier Fly Carcass Flour on Growth and Growth Sangkuriang Catfish (Clarias gariepinus) - Huda J., Muhammad Aidil; Rumondang, Anne; Sarumaha, Herman; Suriyadin, Adi (Jurnal Media Akuakultur Indonesia, 2023)
Sangkuriang catfish (Clarias gariepinus) is a type of freshwater fish which is the prima donna in Indonesia because it grows quite fast compared to other types. Feed is an important component in fish farming activities to support growth. An increase in the price of fish feed without an increase in the selling price of fish is a problem that must be faced by every farmer. Therefore, it is necessary to make efforts to find raw materials that are cheap and easy. The black soldier fly carcass is possible as an alternative to fish meal. Currently, the black soldier fly carcass is not widely used as a raw material for fish feed, even though this type of insect contains a relatively high protein source. The purpose of this study was to examine the potential of adding black soldier fly carcass meal for the growth and survival of Sangkuriang catfish. The black soldier fly carcass has the potential to be used as a substitute for fish meal as much as 50%. The formulated test feed contains 37-38% protein. Test feed performance was compared to control using Duncan's test. After acclimatization, the Sangkuriang catfish size 5-7 cm were randomly stocked into 15 aquariums measuring 100 cm x 50 cm x 51 cm with a stocking density of 25 fish/m3 and were fed 6% of the total weight of all test fish for 35 days. maintenance. The results showed that the growth of Sangkuriang catfish was significantly different between the 50% KL formulation test feed and the control feed (P<0.05). Using black soldier fly carcass meal can increase the absolute weight growth of 3.26 g to 5.22 g and the survival of sangkuriang catfish 77.33 – 86.67%.